Stability analysis of cold-formed channels using mathematical programming techniques - Bedair, Osama (Multidiscipline modeling in materials and structures, 2020)
PurposeIn this work, a numerical algorithm is presented for stability analysis of cold-formed steel (CFS) channel sections.Design/methodology/approachA nonlinear optimization problem is formulated using energy-based technique of idealized channel section subject shear, compression and biaxial bending. The total potential energy is minimized with respect to skew angle and half wavelength of the buckling mode. The optimization algorithm is updated sequentially using quadratic approximation until minimum buckling coefficient is attained. The developed algorithm is validated using other numerical techniques.FindingsThe described algorithm is computationally effective and can be utilized in the industry for analysis of CFS channels under any load combination.Practical implicationsThe paper offers a new tool for engineers in practice to analyze channels subject to combined loadings.Originality/valueVery limited literature dealt with the stability of channels under combined loading. A new numerical algorithm is provided to practitioners to utilize in the industry for analysis of channel sections under combined loading. Unlike finite element or finite strip methods, the channel is not discretized into subelements. Mathematical programming technique is used to find the buckling load. Parametric studies are then carried out to highlight influences of geometric interaction of the channel components and to provide useful guidance to the design of CFS channels.